(untitled) (Advancements in Homeopathic Research, 2025)
Introduction Spine and back problems (SBP) pose significant health and economic burden. Researches have shown positive impact of homeopathy in management of such cases. Rück-Pain® is a homeopathic formulation that has shown promising results in managing chronic SBP. This study aims to evaluate its real-world effectiveness, focusing on pain relief, recovery time, and patient satisfaction. Materials and Methods A Google Form was created to collect feedback on Rück-Pain®’s usage and efficacy. The survey gathered data on prescription distribution, pain relief, recovery time, improvement percentage, and overall satisfaction. The form was distributed through various healthcare channels to ensure broad participation. Results The survey revealed that cervical spondylosis (75 prescriptions) and lumbar spondylosis (33 prescriptions) were the most common conditions treated. The majority of patients (52) recovered in 11-20 days, with 71 patients reporting 51%-75% improvement. Positive feedback was dominant, with 136 positive reviews and only 12 negative reviews, supporting Rück-Pain®’s effectiveness. A large portion of respondents (112) would recommend the product. Discussion The results confirm Rück-Pain®’s efficacy, especially for treating common spinal conditions like cervical and lumbar spondylosis. The varying recovery times are attributed to the chronicity of conditions. Positive feedback, high satisfaction, and recommendation rates underscore the product’s reliability as a back pain remedy. Conclusion Rück-Pain® shows significant effectiveness in treating back pain and related conditions, with high patient satisfaction and rapid improvement. Further research is needed for broader validation.